2021
DOI: 10.1088/1757-899x/1036/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of Emerging Pollutants in Industrial Contaminated Water using Oxytenanthera abyssinica and Bambusa vulgaris in a Treatment Media

Abstract: Remediation of emerging pollutants is an aspect of environmental research with sparse information and knowledge, and the disposal of, these pollutants to the environment are mostly unregulated and on the increase. In view of this, the study examined the adsorptive capacity of adsorbent produced from Oxytenanthera abyssinica (COA 350°C KCl) and Bambusa vulgaris (CBV 350°C H3PO4) in remediating Pharmaceutical actives contaminants (PhACs) and polycyclic aromatic hydrocarbons (PAHs). Fourier Transform Infrared Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…26.25w/w of activator was used in the activation of the carbonated samples. Characterization was done chemically using Point of zero charge (pH pzc) and The Scanning Electron Microscopy (SEM) was used to view the surface structure of the samples at a magnification of 100, 300, 500, 2000, and 5000 times the original size to view the pore space development and reveal other information such as texture (external morphology) and structural orientation see Figure 2 [10]. The point of zero charge (pH pzc) was used for further determination of pore and adsorption capacity.…”
Section: Production Of Local Adsorbent Using Local Technologymentioning
confidence: 99%
See 3 more Smart Citations
“…26.25w/w of activator was used in the activation of the carbonated samples. Characterization was done chemically using Point of zero charge (pH pzc) and The Scanning Electron Microscopy (SEM) was used to view the surface structure of the samples at a magnification of 100, 300, 500, 2000, and 5000 times the original size to view the pore space development and reveal other information such as texture (external morphology) and structural orientation see Figure 2 [10]. The point of zero charge (pH pzc) was used for further determination of pore and adsorption capacity.…”
Section: Production Of Local Adsorbent Using Local Technologymentioning
confidence: 99%
“…One of such is the (PhACs) which are products of synthetic chemicals, natural organic chemicals, or microorganisms not controlled. They possess the ability to penetrate the aquatic environment and alter the natural quality leading to adverse health issues in human and ecological disorders [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 The chemically stable structure of PAHs makes them very persistent compounds in the environment. 32 As a consequence, they can accumulate in remote places 33 and enter the human food chain. 34 It has been demonstrated that these pollutants alter specific and non-specific immunities in fish and mammals 35 and can also affect pregnant women, developing health issues in the embryo.…”
Section: Introductionmentioning
confidence: 99%